FRI0341 Lupus low disease activity state (LLDAS) versus clinical remission as treatment targets in the first 18 months of systemic lupus erythematosus management. (12th June 2018) - Floris, A.; Piga, M.; Cappellazzo, G.; Chessa, E.; Congia, M.; Cauli, A.; Mathieu, A.
Abstract : Background: In the view of applying a treat to target (T2T) strategy in the management of systemic lupus erythematosus (SLE), a novel definition of minimal acceptable disease activity – the lupus low disease activity state (LLDAS) [1] – and clinical remission (CR) [2] were recently proposed. Objectives: To compare attainability and outcomes of LLDAS and CR as treatment targets in the early stages of SLE management. Methods: LLDAS and CR prevalence were analysed at 6 (T1) and 18 (T2) months after treatment initiation (T0) in a monocentric cohort of 107 (median disease duration 9.7 months) prospectively followed Caucasian SLE patients. LLDAS was defined as SLE disease activity index 2000 (SLEDAI-2K)≤4 without major organ activity and no new disease activity, physician global assessment (0–3)≤1, prednisone ≤7.5 mg/day and well-tolerated immunosuppressant dosages. CR was defined as clinical SLEDAI-2K=0 (increased anti-dsDNA and low complement were excluded) and prednisone ≤5 mg/day in patients treated with/without stable immunosuppressants and/or antimalarials. Multivariate models were built to identify factors associated with failure to achieve LLDAS and CR, as well as to investigate relationship between the latter and early damage accrual (defined as SLICC/Damage Index≥1 at T2). Results: LLDAS was achieved significantly more frequently than CR both at T1 [47 (43.9%) vs. 25 (23.4%); p<0.001] and T2 [48 (44.9%) vs. 35 (32.7%); p<0.001]. Out patients achieving LLDAS, 25 (53.2%) and 35 (66.7%) concomitantly fulfilled the criteria for CR at T1 and T2, respectively. A prednisolone (PDN) dose exceeding the minimal acceptable range set in the respective definitions was the most frequent reason for failure to achieve both LLDAS and CR (in 83.0% of no-LLDAS patients at T1% and 95.1% of no-CR at T1). The disease manifestations with the highest persistence rate during follow-up were: increased anti-dsDNA (persistently present in 85.7% and 67.5% of cases at T1 and T2, respectively), low complement (73.2% and 66.3%) and renal abnormalities (46.4% and 28.6%). Renal involvement at baseline significantly associated with failure to achieve LLDAS both at T1 (OR: 7.8, 95% CI: 1.41–43.40; p=0.019) and T2 (OR: 3.87, 95% CI 1.41–10.6; p=0.008) and CR at T2 (OR 9.46, 95% CI 1.13–78.8). High PDN dosage was significantly associated with no-CR achievement both at T1 (OR 6.23, 95% CI 2.2–18.3; p=001) and T2 (OR 1.11, 95% CI 1.02–1.20; p=0.02). Early damage was recorded in 23 (21.5%) patients and was significantly associated, on multivariate analysis, with older age at diagnosis (OR 1.05 95% CI 1.01–1.09; p=0.016) and failure to achieve LLDAS (OR 4.82, 95% CI 1.44–16.09; p=0.11) at T1. No significant association was found between early damage and failure to achieve CR, possibly due to its low prevalence among this cohort of early SLE patients. Conclusions: During the early stages of SLE, LLDAS and CR overlap definitely less frequently than reported in long-standing disease (53.2%–66.7% vs 83.9%–96.5% [2] ). Although remission is recommended as the primary treatment target in SLE, LLDAS may represent a valid alternative in the first stages of disease management, being more attainable compared to CR and negatively associated to early damage. References: [1] Franklyn K, et al. Ann Rheum Dis2016;75:1615–21. [2] Zen M, et al. Ann Rheum Dis2017;76:562–5. Disclosure of Interest: None declared